A high performance grid synchronization method for renewable energy grid-connected applications - Nanmu Hui (Elsevier, 2021)
Aiming at the problem of insufficient harmonic suppression capability for distributed renewable energy grid-connected application equipments, an efficient grid synchronous phase-locked loop(PLL) which will suppress harmonics is proposed. Firstly, a novel high-order generalized integral (NHOGI) is presented in traditional αβ-frame, and the dual novel high-order generalized integral (DNHOGI) structure is presented. Secondly, to remove interference of harmonic on PLL, a moving average filter(MAF) is added to eliminate the multi-order harmonic components and improve the phase-locked accuracy. Finally, DNHOGI and MAF filters are combined into a cascade filter, and a phase-locked loop used the cascade filter is proposed. The feasibility of the new approach is tested by experimental comparison with traditional methods.